2016
DOI: 10.1080/19419899.2016.1168312
|View full text |Cite
|
Sign up to set email alerts
|

Attachment orientation and sexual risk behaviour among young Black gay and bisexual men

Abstract: This mixed methods study used an explanatory sequential design to examine the relationship between attachment and sexual behavior among young Black gay and bisexual men (YBGBM). Cross sectional online surveys and sex diaries were completed by a sample of YBGBM in New York City (n = 153) to assess the association between adult attachment insecurity and sexual risk behavior. The Experiences in Close Relationships Scale-Revised (ECR-R) was used to assess three types of adult attachment (i.e., secure, anxious, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Our results are partially supported by other scholars who have found that adult attachment avoidance and anxiety are associated with the increased likelihood that YBGBM will report experiencing childhood trauma and poor mental health during young adulthood (Cook, Watkins, Calebs, & Wilson, 2016). More specifically, it may be that YBGBM develop maladaptive coping strategies in response to their childhood traumatic experiences that are associated with future poor mental health.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are partially supported by other scholars who have found that adult attachment avoidance and anxiety are associated with the increased likelihood that YBGBM will report experiencing childhood trauma and poor mental health during young adulthood (Cook, Watkins, Calebs, & Wilson, 2016). More specifically, it may be that YBGBM develop maladaptive coping strategies in response to their childhood traumatic experiences that are associated with future poor mental health.…”
Section: Discussionsupporting
confidence: 88%
“…More specifically, it may be that YBGBM develop maladaptive coping strategies in response to their childhood traumatic experiences that are associated with future poor mental health. This line of thought comes partially from the attachment research literature, which specifies the close association between adult attachment anxiety and maladaptive coping strategies (Cook, Watkins, Calebs, & Wilson, 2016). This is only one plausible explanation for our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by extant research (Newcomb et al, 2014). Further, these increases in condomless anal sex have been linked to the need to explore sex and sexuality during the emerging adulthood period (Cook, Watkins, Calebs, & Wilson, 2016). Indeed studies have found that as emerging adult gay and bisexual men become more comfortable with their sexual identity and are more comfortable with exploring different sexual situations, they are able to more fully explore different sexual partnerships (Diamond & Lucas, 2004; Gamarel, Comfort, Wood, Neilands, & Johnson, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Lisa Bowleg, Stephanie Cook, and others have championed the need to consider the diversity among sexual identities, experiences, and orientations of Black men ( Bowleg, 2013 ; Bowleg et al, 2016 ; Bowleg et al, 2013 ; Cook, Watkins, Calebs, & Wilson, 2016 ; Wilson et al, 2016 ). This work has been critical in highlighting how the intersection of these identities further complicates the categories or identities that remain marginalized and invisible, and how men embody gender in the context of dynamic cultural ideals and social structures in ways that create new configurations of practice, in particular, local situations and contexts, whereby diverse groups of men are negotiating different ways of being their own gendered selves ( Lusher & Robins, 2009 ).…”
Section: Centering the Margins: The Promise Of Intersectionality In Mmentioning
confidence: 99%